Does post-acute COVID-19 syndrome women's sex problems link to psychiatry after 6 months? - Rofaida Refaat Shehata; Gellan K. Ahmed; Aliae A. R. Mohamed Hussien; Manal A. Mahmoud (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Background Few data about women's sexuality practices post-acute COVID-19 syndrome are available. Many women who have had the disease experience sexual dysfunction; hence, the adverse effect of COVID-19 on sexual function has generated interest. We aimed to clarify the impact of COVID-19 on female sexual function 6 months after the illness and possible risk factors and to evaluate the relationship between psychiatric problems and female sexual dysfunction 6 months after COVID-19. Sixty-two patients were enrolled in this cross-sectional study and assigned according to female sexual function index scores to two groups: those with and without sexual dysfunction. For all participants, we documented socioeconomic status, sexual history, symptoms of COVID-19, vaccination data, and Symptom Checklist 90. Results Sexual dysfunction was 58% of all participants after 6 months COVID-19. Sexual frequency and sexual problems except pain were decreased in both groups with more affection in sexual dysfunction women. Sexually dysfunctional women were more likely to obtain oxygen therapy during COVID-19, received AstraZeneca, had post-vaccination myalgia and headache, and recurring COVID-19 after vaccination. No significant SCL-90 subscale differences. Sexual dysfunction was associated with renal illness, fatigue, COVID-19-related oxygen therapy, post-vaccination myalgia, and headache. Conclusions After 6 months COVID-19, there was a decline in the frequency of sexual intercourse and scores on all FST subscales in both groups except pain, with more affection in sexual dysfunction women. No statistical difference in psychiatric problems between both groups. Sexual dysfunction was associated with renal illness, COVID-19-related oxygen therapy and fatigue, post-COVID-19-vaccination myalgia, and headache.